EXPERT SYSTEM TO DIAGNOSE DIGESTIVE DISEASES USING CERTAINTY FACTOR - Mellya Rindhani Aditia; Dinda Djesmedi; Fitri Firdalius; Hari Marfalino (STMIK Royal, 2022)
Abstract: Tract disorders are disorders caused by abnormalities in the digestive system. This disorder is triggered by food or a person's physical condition. Digestive disorders cannot be diagnosed quickly, but mostly occur in the digestive system. Because the knowledge that will be suspected as a disease is still lacking, it takes experts or doctors to diagnose digestive disorders. The goal is to help produce a diagnosis of the disease experienced by the patient based on the symptoms experienced. The research data is processed based on the symptoms felt by the patient. Patient data using the Certainty Factor method or the value of disease certainty. This Certainty Factor method is a system that is able to run according to needs and produces a high percentage of accuracy results. The system design stage is implemented in the Hypertext Preprocessor programming language and My SQL database. The results of the diagnosis with this method produce a level of confidence in the patient's disease. From the results of the tests carried out, it can produce information about the diagnosis of the disease and help patients and medical personnel in knowing the condition of the disease that is being experienced. Keywords: certainty factor; digestive tract disorders; expert system, Abstrak: Gangguan saluran merupakan gangguan yang disebabkan oleh kelainan pada sistem pencernaan. Gangguan ini dipicu oleh makanan atau kondisi fisik seseorang. Gangguan pencernaan ini tidak bisa dilakukan diagnosa dengan cepat, tetapi sebagian besar terjadi pada sistem pencernaan. Dikarenakan pengetahuan yang akan diduga sebagai penyakit masih kurang, maka dibutuhkan tenaga ahli atau dokter untuk mendiagnosis gangguan pencernaan. Tujuannya untuk membantu menghasilkan diagnosa penyakit yang dialami pasien berdasarkan gejala yang dialami. Data penelitian diolah berdasarkan gejala yang dirasakan oleh pasien. Data pasien menggunakan metode Certainty Factor atau nilai kepastian penyakit. Metode Certainty Factor ini merupakan sistem yang mampu berjalan sesuai dengan kebutuha serta menghasilkan persentase akurasi hasil yang tinggi. Tahapan perancangan sistem diimplementasikan ke dalam bahasa pemrograman Hypertext Preprocessor dan database My SQL. Hasil diagnosa dengan metode ini menghasilkan tingkat kepercayaan terhadap penyakit pasien. Dari hasil pengujian yang dilakukan sudah dapat menghasilkan informasi tentang diagnosa penyakit dan membantu pasien serta tenaga medis dalam mengetahui kondisi penyakit yang sedang dialami. Kata kunci: certainty factor; gangguan saluran pencernaan; sistem pakar